Alat Bantu Jalan Tunanetra Menggunakan Sensor Light Detection And Ranging (LiDAR) berbasis Arduino - Aryani, Dharma; Gunawan, Arya Irfan; Reski, Reski; Nisa, Khairun; Zubair, Achmad (Jurnal Teknologi Elekterika, 2023)
Walking stick is very important for the visually impaired person. It can help the visually impaired to walk more easily and to navigate the environment feeling safe and confident. Therefore, a cane that can detect object or obstacle is designed using Arduino microcontroller combined with a Light Detection And Ranging (LiDAR) sensor as an obstacle or object detector. Lidar sensors are utilized in visually impaired walkers equipped with notifications and warnings in the form of buzzer sounds and vibrations when obstacles and objects are detected. The walking stick is functioned in three conditions based on the distance of the stick and the object. For distance of 0 to 45 cm, the stick vibrates and emit a sound that reminds the user for the presence of an object. In medium distance, which is a range of 45 to 75 cm, the vibration exist with additional buzzer sound every second will occur i. Furthermore, the stick only vibrates if the object is detected in a distance of 75 to 100 cm. This walking stick can help the visually impaired in carrying out activities more safely and reduce the risk of accidents to users